A COMPREHENSIVE ANALYSIS OF GLOBAL HEALTH CHALLENGES: PUBLIC HEALTH INTERVENTIONS, VACCINE DISTRIBUTION HURDLES, AND THE SOCIO-ECONOMIC ROOTS OF HEALTH DISPARITIES - ‏EssamGharamahAl Ghamdi, MashariAayadhAlotaibi, Khaled Nasser Alotaibi, Mansour MeshalBijadAlotaibi, Fatimah MufadhiAlanazi, Amal Hussain Asiree, Salem MofarehAl Malki, AeshahSaeed MufakkirAl Mutairi (Chelonian Research Foundation, 2023)
The unprecedented challenges posed by recent global health crises, notably the COVID-19 pandemic, have underscored the critical need for effective public health interventions, equitable vaccine distribution mechanisms, and a deeper understanding of the socio-economic determinants contributing to health disparities worldwide. This article critically reviews the landscape of public health strategies employed to combat infectious diseases, the logistical and ethical hurdles in vaccine distribution, and the pervasive impact of socio-economic factors on global health disparities. By synthesizing current research, policy analyses, and case studies, the review highlights the interconnectedness of these domains and advocates for an integrated approach to health policy and practice. The findings suggest that addressing the complex web of factors influencing global health requires a multifaceted and coordinated effort from governments, international organizations, and civil society. The review concludes with recommendations for policy reforms and future research directions aimed at fostering more resilient public health systems and narrowing the health equity gap. Keywords: Public Health Interventions, Infectious Diseases, Vaccine Distribution, Health Disparities, Socio-Economic Determinants, Global Health Challenges, Equity in Healthcare, Health Policy